1996
DOI: 10.1007/bf00144618
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the involvement of nitric oxide in cisplatin-induced toxicity in rats

Abstract: Cisplatin treatment of rats results into a significant increase in the activity of Ca(2+)-independent nitric oxide synthase (NOS) in kidneys and liver. Significant enhancement of lipid peroxidation in gastric mucosa, kidneys and liver was also observed. The administration of NG-nitro-L-arginine methyl ester, an inhibitor of NOS, markedly reduced renal and gastrointestinal toxicity, and also decreased the content of blood urea nitrogen, serum creatinine, and incidence of diarrhoea along with a significant inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 18 publications
4
45
1
Order By: Relevance
“…The interaction of ROS with cellular components may result in damage to biomolecules, including DNA, proteins, and lipids. Cisplatin treatment also induces a significant increase in the activity of calcium-independent nitric oxide synthase in rat kidney and liver tissues, resulting in an increase in serum NO levels as well as in tissue NO formation (40,41). Peroxynitrite, which is generated by the reaction between nitric oxide and superoxide anion, also oxidizes biomolecules.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of ROS with cellular components may result in damage to biomolecules, including DNA, proteins, and lipids. Cisplatin treatment also induces a significant increase in the activity of calcium-independent nitric oxide synthase in rat kidney and liver tissues, resulting in an increase in serum NO levels as well as in tissue NO formation (40,41). Peroxynitrite, which is generated by the reaction between nitric oxide and superoxide anion, also oxidizes biomolecules.…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin treatment also causes a significant increase in the activity of the calcium-independent nitric oxide synthase (NOS) in rat kidney and liver, leading to an increase in serum NO level as well as in tissue NO formation. 30,31) Peroxynitrite, generated by the reaction between nitric oxide and superoxide anion, oxidizes biomolecules such as DNA, proteins and lipids. In the present study, the oral administration of the licorice extract in combination with the cisplatin treatment prevented the increases in the serum nitric oxide and tissue lipid peroxidation levels, and significantly recovered the tissue GSH level and antioxidant enzyme activities in the cisplatin-treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that inhibition of these enzymes may lead to an increase in levels of arginine, an immediate substrate for nitric oxide synthase (NOS), producing a nitric oxide (NO) precursor that can lead to the formation of NO. A role for NO has been implicated in models of renal injury (Srivastava et al 1996), and L-arginine has been demonstrated to be both protective (Andoh et al 1997) and harmful (Tome et al 1999) in models of renal injury. The authors speculate that although the initial effects of NO formation after renal injury may be beneficial, the prolonged inhibition of the L-arginine pathway may contribute to renal damage because of excessive buildup of NO, which has been implicated in numerous renal pathologies (Valdivielso and Blantz 2002).…”
Section: Discussionmentioning
confidence: 99%